Bending impact behaviour of sandwich beams with expanded polystyrene foam core: Analysis. (January 2019) - Caliskan, Umut; Apalak, M Kemal
This study addresses the bending impact behaviour of sandwich beams made of a low density core bonded to two metal face sheets under low-velocity impact. The geometrical and material non-linearities were considered in the explicit dynamic analysis. The face sheets and core were made of aluminum and expanded polystyrene foam. The effects of design parameters, such as foam density, foam thickness, plate thickness, on the impact energy absorption of the joint were investigated. The foam material was modelled as a crushable foam material, and the cohesive response of the adhesive interface was analysed using the cohesive zone model. Experimental low-speed impact tests were carried out to validate the finite element analysis, and the temporal variations of the contact force and the permanent central deflections at the top and bottom faces of the sandwich beams were in good agreement.